Provenance of Kinet Höyük Ceramics Uncovered in Excavations: Petrography, XRF and Raman Analysis - Eroğlu, Murat; Deniz, Kıymet; Kadıoğlu, Yusuf Kağan; Gates, Marie-Henriette (Zenodo, 2022)
The archaeological finds unearthed at Kinet Höyük are a sensitive indicator of the forces that shaped the economic relationship in the Eastern Mediterranean during these centuries. Among the archaeological finds, pottery is especially important evidence for the determination of cultural and economic relations at important chronological moments. Petrographic, XRF (X-rays fluorescence) and Raman analysis techniques were used to determine the mineralogical-petrographic and chemical contents of the pottery selected from stratified levels dating to the Bronze Age, Iron Age and Hellenistic Period unearthed during the excavations at Kinet Höyük and clay samples taken from the environment. It was determined that some of the studied samples were compatible with the samples taken from the regional geological formations and clay beds, and it was determined that they were local production.
Keywords: Engineering; Kinet Höyük, Ceramics, Provenance, Petrographic, XRF, Raman; Mühendislik; Kinet Höyük; Ceramics; Provenance; Petrographic; XRF; Raman